Sustainability Assessment of Rural Water Supply System in Lamongan, Indonesia - Rizka Novembrianto; Restu Hikmah Ayu Murti; Muhammad Abdus Salam Jawwad; Syadzadhiya Qothrunada Zakiyayasin Nisa’ (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2023)
The commitment to provide clean water and proper sanitation is one of the goals of the Sustainable Development Programs (SDGs). The government of each region needs to strive for clean water for the community. Efforts to provide clean water can be realized with the Water Supply System. Water Supply System sustainability indicators need to fulfill three aspects of quality, quantity, and continuity. The aim of this research was to assess the sustainability of the ‘Sugio’ Water Supply System in Lamongan Regency, which served three villages, namely Sugio, Lebakadi, and Sekarbagus. The aspect of water quality, seen from the results of the analysis of the quality of production water, met the quality standards for drinking water. The aspect of water quantity was calculated to meet water needs for the next 20 years. The calculation showed that the daily average debit requirement was 17 L/s and the daily maximum debit was 19 L/s, while the existing debit was 15 L/s. The aspect of water continuity was calculated by the ability to distribute water during an emergency. The calculation showed that the distribution of clean water when there was no source of electrical energy could only be carried out in a maximum of 1 hour, 13 minutes, and 48 seconds. The conclusion obtained was that the sustainability of the ‘Sugio’ Water Supply System from the perspective of water quantity and continuity needed to be improved.